Oral health knowledge of parents of children and adolescents with congenital heart disease - Caroline Louise Sampaio PINHEIRO; Ana Cláudia Lima de Oliveira MEIRA; Aline Silva dos SANTOS; Delson Araujo SILVA (Faculdade São Leopoldo Mandic, 2019)
To assess the knowledge on oral hygiene, infective endocarditis, and antibiotic prophylaxis of parents of children and adolescents with heart diseases assisted at the Hospital Ana Nery (reference hospital), Salvador, Bahia, Brazil. Cross-sectional study with 43 guardians of children and adolescents aged 2 through 16 years, performed with the application of a questionnaire. In the sample of parents studied, 64% had completed high school and 47% had a monthly family income of up to one minimum wage. The majority (81%) reported knowing that oral infections may lead to heart complications, 42% knew that oralbacteria may migrate to the heart, and 51% knew the term infective endocarditis. When questioned about antibiotic prophylaxis, 93% had no knowledge about it and 88% did not know the reasons for using antibiotics before dental treatment. Parental knowledge was limited and fragmented. Further attention is required when transmitting information to parents, focusing on prevention strategies in order to guarantee the integral health of these children and adolescents.